Student satisfaction on service quality: a study at Malaysian public university - Zakaria, Nur Hamizah; Sulong, Muhammad Suhaimi; Abdul Hamid, Norashikin (ANP, 2022)
Students will engage in informal learning outside the lecture hall in addition to the formal learning. The Universiti Tun Hussein Onn Malaysia (UTHM) Centre’s for General Studies and Co-curriculum (PPUK) is a division that provides services focused on activities outside the lecture hall. Issues, particularly student satisfaction, become a critical concern for PPUK management as a result of these actions. The crucial element is determining the level of student satisfaction with PPUK's services where students have difficulty carrying out activities outside the lecture hall due to problems with the quality of services supplied by PPUK involving Credited Co-Curricular Courses (KKB) that the university has scheduled. As a result, if the services provided are unsatisfactory, which will have an indirect negative impact on the student's satisfaction as a student. The purpose of this study was to determine students' perceptions of satisfaction with the services provided by PPUK, UTHM based on the SERVQUAL Model's five dimensions (physical evidence, responsive, empathy, guarantee, and trustworthiness). The study is designed in the form of a survey, with data collected via a questionnaire. The researcher focused on UTHM students who registered for KKB in the second semester for this study. To answer the research questions, the data were analysed using the Statistical Package for the Social Sciences (SPSS) software to measure the frequency, mean score, t-test, and correlation of each element. Overall, the results show that students are extremely satisfied with the services provided by the PPUK UTHM. Other inferential and regression analyses will be investigated further and improved to the PPUK curriculum.